A decentralized paradigm for resource-aware computing in wireless Ad hoc networks - Heerok Banerjee; S. Murugaanandam; V. Ganapathy (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
A key factor limiting the democratisation of networked systems is the lack of trust, particularly in the wake of data-intensive applications that work on sensitive and private data, which requires providing strong network security guarantees via encryption and authentication algorithms, as well as rethinking algorithms to compute on the network peripheries without moving data. In many security and privacy-critical domains such as Home Automation IoT networks, AUV networks etc., the existence of a centralized privileged node leads to a vulnerability for leakage of sensitive information. In this paper, we have proposed a decentralized networking architecture that adopts collaborative processing techniques and operates within the tradeoff between network security and performance. We have investigated the design and sustainability of autonomous decentralized systems and evaluated the efficiency of the proposed scheme with the help of extensive simulation tools.